2013
DOI: 10.1186/1471-244x-13-339
|View full text |Cite
|
Sign up to set email alerts
|

EXPLAIN Fragile-X: an explorative, longitudinal study on the characterization, treatment pathways, and patient-related outcomes of Fragile X Syndrome

Abstract: BackgroundFragile X syndrome (FXS), caused by a mutation of the FMR1 gene on the X chromosome, is the most common inherited form of intellectual disability and autism spectrum disorders. Comprehensive data are lacking, however, on the characteristics and management patients with FXS in Germany.Methods/designEXPLAIN is a prospective, observational, longitudinal registry with a non-probability sampling approach. It collects data on patient characteristics, therapeutic interventions, psychosocial parameters (incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…For example, the data collection tools used in FORWARD were shared with a group of fragile X clinicians and researchers in Germany working to create a similar data resource, referred to as EXPLAIN. 44 The potential outcome will be the ability to compare and contrast clinical outcomes of FXS in different clinical and cultural settings. Use of the same tools and variables in longitudinal studies of other neurologic disorders will also increase understanding of the commonalities among ID and behavioral disorders and potentially lead to new discoveries.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the data collection tools used in FORWARD were shared with a group of fragile X clinicians and researchers in Germany working to create a similar data resource, referred to as EXPLAIN. 44 The potential outcome will be the ability to compare and contrast clinical outcomes of FXS in different clinical and cultural settings. Use of the same tools and variables in longitudinal studies of other neurologic disorders will also increase understanding of the commonalities among ID and behavioral disorders and potentially lead to new discoveries.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the study protocol have been reported earlier [21]. The study was conducted in accordance with the local laws and regulations [22, 23].…”
Section: Methodsmentioning
confidence: 99%
“…The present study is a prospective observational (non-interventional) study (registry) in Germany. Details of the study protocol have been reported earlier [ 21 ]. The study was conducted in accordance with the local laws and regulations [ 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Eine systematische Erfassung von klinischen und psychosozialen Charakteristika der Betroffenen sowie Behandlungswegen fehlt in Europa. Genau diese Erfassung hat die Studie FragilE X Registry: An exPlorative Longitudinal study for chAracterization, treatment pathways and patient-related outcomes (EXPLAIN) zum Ziel [6].…”
unclassified